2005
DOI: 10.1111/j.1708-8208.2005.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Treatments with Implant-Supported Maxillary Overdentures

Abstract: Maxillary implant-supported overdentures show a high implant failure rate, but fewer implant failures occurred for patients originally planned for overdenture treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 12 publications
2
41
1
1
Order By: Relevance
“…In contrast, patients who were initially planned for maxillary implantsupported prostheses had low implant failure rates [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, patients who were initially planned for maxillary implantsupported prostheses had low implant failure rates [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, literature has claimed that complete palatal coverage would be more beneficial since it would reduce the wear of the abutments and minimize the risk of fracture of the prosthesis base [33,45]. This risk of fracture can be decreased using framework reinforcement for the IOD, and it must have a suitable design and thickness to allow sufficient thickness for the acrylic resin [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…concluded in a study of IODs ( n = 13) and IFDs ( n = 14), a follow-up of an average of 5.7 years and 5.5 years, respectively; the cumulative survival of the implants was 77% for IODs and 46% for IFDs, and the probability of having implant failure was 3 times higher in IFDs than IODs. [17]…”
Section: Discussionmentioning
confidence: 99%
“…[17] It was suggested that the IOD occlusal load is distributed more favorably when the implants are immobilized using a rigid bar compared to separated implants using the ball system. [21] However, Bressan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with bar supported implant overdentures may develop mucosal hyperplasia beneath the bar and mucositis around the implants. [910111213141516] Reduced tissue coverage of unsplinted, free-standing attachments such as Locators (Zest Anchors) or ERA attachments (Sterngold) make them a better treatment choice than connected bars for patients with poor oral hygiene. [7]…”
Section: Introductionmentioning
confidence: 99%